Catalytic upgrading of lactose: a rest raw material from the dairy industry. Issue 8 (28th March 2017) - Zaccheria, Federica; Mariani, Matteo; Scotti, Nicola; Psaro, Rinaldo; Ravasio, Nicoletta
Abstract : Lactose, a residue from the separation of high value-added proteins from whey, was converted into an equimolar mixture of sorbitol and dulcitol through a one-step cascade hydrolysis plus hydrogenation process. Abstract : Lactose, a residue from the separation of high value-added proteins from whey, was converted into an equimolar mixture of sorbitol and dulcitol through a one-step cascade hydrolysis plus hydrogenation process. The reaction was promoted by an amorphous copper on silica catalyst, highly resistant to water and can also be applied to other disaccharides. The process selectivity can be switched to direct hydrogenation of lactose to lactitol only by changing the solvent.